Case Report: Benign Phyllodes Tumor of the Vulva. Issue 2 (March 2020) - Vella, Josefa E.O.; Thomas, Michael P.; Singh, Ruchira; Shaaban, Abeer M.
Abstract : Abstract: Phyllodes tumor of the vulva is a rare tumor and is histologically similar to phyllodes tumor of the breast. Morphological and immunohistochemical features of a case are presented here.